Cloning and characterisation of the S. pombe rad15 gene, a homologue to the S. cerevisiae RAD3 and human ERCC2 genes. - Murray, J M (1992)
The RAD3 gene of Saccharomyces cerevisiae encodes an ATP-dependent 5'-3' DNA helicase, which is involved in excision repair of ultraviolet radiation damage. By hybridisation of a Schizosaccharomyces pombe genomic library with a RAD3 gene probe we have isolated the S. pombe homologue of RAD3. We have also cloned the rad15 gene of S. pombe by complementation of radiation-sensitive phenotype of the rad15 mutant. Comparison of the restriction map and DNA sequence, shows that the S. pombe rad15 gene is identical to the gene homologous to S. cerevisiae RAD3, identified by hybridisation. The S. pombe rad15.P mutant is highly sensitive to UV radiation, but only slightly sensitive to ionising radiation, as expected for a mutant defective in excision repair. DNA sequence analysis of the rad15 gene indicates an open reading frame of 772 amino acids, and this is consistent with a transcript size of 2.6 kb as detected by Northern analysis. The predicted rad15 protein has 65% identity to RAD3 and 55% identity to the human homologue ERCC2. This homology is particularly striking in the regions identified as being conserved in a group of DNA helicases. Gene deletion experiments indicate that, like the S. cerevisiae RAD3 gene, the S. pombe rad15 gene is essential for viability, suggesting that the protein product has a role in cell proliferation and not solely in DNA repair.